Day 1 Tue, January 24, 2023 2023
DOI: 10.2118/212638-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Tight Sandstone: Effect of Clay Mineralogy on Pore-Framework

Abstract: Macro-, meso-, micro-pore systems combined with clay content are critical for fluid flow behavior in tight sandstone formations. This study investigates the impact of clay mineralogy on pore systems in tight rocks. Three outcrop samples were selected based on their comparative petrophysical parameters (Bandera, Kentucky, and Scioto). Our experiments carried out to study the impact of clay content on micro-pore systems in tight sandstone reservoirs involve the following techniques: Routine core analysis (RCA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…It ought to be mentioned that the micropore system represented a significant proportion of the tight rock's total porosity [88,89]. Our study confirmed that the micropore systems of the studied sandstones significantly contributed to overall sandstone porosity, with contributions of 38% in the Bandera, 48% in the Kentucky, and 50% in the Scioto samples.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It ought to be mentioned that the micropore system represented a significant proportion of the tight rock's total porosity [88,89]. Our study confirmed that the micropore systems of the studied sandstones significantly contributed to overall sandstone porosity, with contributions of 38% in the Bandera, 48% in the Kentucky, and 50% in the Scioto samples.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, the low clay content of the other sandstones (50.1% for Scioto and 48% for Kentucky) leads to the presence of high micropore-system proportions, and to the relatively high contribution of the micropore-throat system (60% for Scioto and 50.9% for Kentucky sandstone). It ought to be mentioned that the micropore system represented a significant proportion of the tight rock's total porosity [88,89]. Our study confirmed that the micropore systems of the studied sandstones significantly contributed to overall sandstone porosity, with contributions of 38% in the Bandera, 48% in the Kentucky, and 50% in the Scioto samples.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation